The role of glycosylation in allergen recognition - Al-Ghouleh, Abeer (2011)
This project is an attempt to have a better understanding of the role of carbohydrates in recognition and uptake of allergens by the innate immune system. Glycosylation analysis of different allergens like Der p 1, Fel d 1, Ara h 1, Ber e 1, Der p 2, Bla g 2, Can f 1, Bromelain and Papain was made using labelled lectins that can detect specific carbohydrate moieties on proteins to reveal their pattern of glycosylation. These experiments showed that all major allergens are glycosylated and this represented a major first step towards demonstrating a link between glycosylation and allergen recognition by the innate immune system. N- and O-glycosylation patterns were predicted in different allergens and a difference in mannosylation and fucosylation was detected between allergens and non-allergenic proteins. We found that the main dominant sugars on allergens are 1,2 1,3 and 1,6 mannose, as detected by GNA lectin. We have also showed that Der p 1 and Der p 2 possess 1,3 fucose in their natural forms, thus concluding that Der p1 and Der p 2 have part of the CCDs which are epitope structures for IgE. O-glycosylation in allergens was also studied giving a better understanding of the whole glycan structure in allergens.